ROLE OF RELIGIOUS AFFAIRS OFFICE OF RANTAU UTARA DISTRICT IN DISSEMINATION OF LAW NUMBER 16 OF 2019 CONCERNING EARLY MARRIAGE - Romadani Simbolon; M. Yoserizal Saragih (KABILAH : Journal of Social Community, 2022)
Abstract: This study aims to find out the role of Public Relations (PR) of the Office of Religious Affairs (KUA) of Rantau Utara District in socializing the law on early marriage. As a theoretical basis in analyzing the problems in this qualitative research, theories about public relations and public relations communication management are used, so that researchers are required to obtain data and information by conducting in-depth interviews and observations. This research uses a qualitative approach that is descriptive. The informant in the research was Mr. Muhammad Ikhwan Lubis who served as chairman of the Office of Religious Affairs in Rantau Utara District. The data collection technique used by the researcher was to conduct interviews, observation and documentation, using a phenomenological study approach, in which the researcher tried to find the meaning of the phenomenon of the role of public relations in socializing the law on early marriage at the KUA of Rantau Utara District. The data analysis used by the researcher is descriptive analysis, which summarizes all the data that has been collected from the interviews. The results of this study indicate that in socializing the law on early marriage, the Public Relations Office of the North Rantau Sub-District conducted special training for young people, and socialization as well as direct counseling to educate the public in North Rantau District. Keywords: Public Relations Role, Office of Religious Affairs, Law, Early Marriage